Drospirinone: new generation of progestogen (Faculty of Medicine Universitas Indonesia, 2005)
Drospirinone is a new generation of progestogen that possesses antimineralocorticoid effect. Progestogen of this type has been used as a component in combined contraceptives. The combined contraceptives of old generation contained progestogen component of testosterone derivative. Progestogen of this type does not have antimineralcorticoid effect, such that it could cause fluid retention. As a result, women who used combined pills of this type often complained of headache, breast pain, calf pain, increased body weight and blood pressure. Owing to its androgenic effect, combined contraception pills that contained testosterone-derived progestogen may cause acne and oily face. Combined contraception that contains drospirinone does not cause headache, breast pain, calf pain, increased body weight and blood pressure. Drospirinone has such a strong anti-androgenic nature that it does not result in acne and oily face. In addition, combination of ethinylestradiol and drospirinone can be used for treating pre-menstrual syndrome and menstrual pain. Drospirinone does not affect lipid and carbohydrate metabolism. (Med J Indones 2005; 14: 190-3)